RESPONSE OF COWPEA TO THE SPRAYING OF BORON AND CARBO LIZER ON GROWTH AND YIELD OF GREEN PODS - & Hanshal, Al-bayati (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
An experiment was carried out at the vegetable fields of Horticulture and Landscaping Design Dept. , College of Agriculture / university of Baghdad / Abu Ghraib at season (2014) to study the effect of spraying boron and Carbo lizer on growth and yield of cowpea. (Ramshorn C.v.) Seeds are sown at two dates; Spring and summer date. The experiment also included the use of four concentrations of Boron (B), which were; (0, 50, 100 and 200) mg. L-1 and three concentrations of Carbo lizer; (c) (0, 1,25 and 2,5) cm3.L-1 sprayed at three times; (30, 45 and 60) days after sowing. The experiment analysis is carried out in accordance to the experimental design RCBD and it is adopted in three replacements, and it is compared with at least L.S.D. significant probability level at 0.05.The treatment B1 show a significant increase in leaves number (27.4 leaf.plant-1), leaf area (212.3dm2.plant-1), dry weight for the total vagitative (43.0 g.plant-1 ), day number to flower 50% plants(47.3 days), pod number ( 42.56 pod.Plant-1), yield of green pods (127.5 gm.plant-1), total yield of green pods (6.800 ton.ha-1 ) respectively in spring season, While The treatment B3 show a significant increase in leaves number (38.6 leaf.plant-1), leaf area (252.9 dcm2.plant-1), dry Weight for the total vagitative (113.9 g.plant-1 ), day number to flower 50% plants(56.8 days), pod number (100.54 pod.Plant-1), yield of green pods (300.9 g .plant-1), total yield of green pods (16.084 Ton.ha-1 ) respectively in summer season , While The treatment C1 show a significant increase in number (37.5,28.1 leaf.plant-1), leaf area (240.1,218.2 dcm2.plant-1), pod number (98.39,40.66 pod.Plant-1), yield of green pods (287.0,122.2 g.plant-1), total yield of green pods (15.304,6.519 Ton.ha-1 ) for both seasons respectively The interaction treatment B1C1(50 mg.L-1 Boron +1.25 cm3 Carbo lizer) in spring season, and B3C1 (200mg L-1 Boron+1.25 cm3 Carbo lizer) in summer season show a significant increase of leaves number (30.7,40.3)leaf.plant-1, leaf area (265.5, 258.4) dcm2.plant-1, dry weight for the total vegetative (47.7, 122.1) g.plant-1, day number to flower 50% plants(47.0,53.7)days, pod number ( 55.43,113.03) pod.Plant-1, yield of green pods (161.9, 316.3) g.plant-1, total yield of green pods (8.632, 16.871) Ton.ha-1 respectively, this is in comparison with the control plant which gave(20.0,28.3 leaf.plant-1),(143.9,182.1 dcm2.plant-1), (32,4, 80.4 g.plant-1),(48.7,59.3 days) (27.17, 70,83 pod.Plant-1), (82.2, 210.3 g.plant-1), (4.385, 11.216 Ton.ha-1) respectively and for both dates respectively.